MAPA [postal fragments] (Palíndromo, 2025)
MAPA [postal fragments] is a visual and sound essay that develops writing in an expanded field by combining field research photographs, cartographies with factual data, and three postcards – black and white images (front) and a synopsis with a QR code to listen to a sound composition with archives (back). Each postcard can be read as a territorial and poetic cutout of a broader research. MAPA [this mouth that fails with the toxic names it ruminates] deals with the list of pesticides available for use in Brazil. Starting in 2020, each section is dedicated to the corresponding letter of the alphabet and articulates sounds produced by human and non-human bodies, devices and aspects of the geopolitical scenario, environmental contexts, images, and archival practices. MAPA (I) Ministry of Agriculture, Livestock, and Supply; (II) Territory design, cartography; (III) Imaginary of things that enter our mouths and the words we lack in the face of Brazil's socio-environmental policies. How do toxic names and organic sounds compose traces and deviations, build and destabilize images?
Keywords: Image; Sound; Writing; Pesticides